2015
DOI: 10.1103/physrevlett.115.133001
|View full text |Cite|
|
Sign up to set email alerts
|

Resonance Effects in Photoemission Time Delays

Abstract: Abstract:We present measurements of single-photon ionization time delays between valence electrons of argon and neon using a coincidence detection technique that allows for the simultaneous measurement of both species under identical conditions. Taking into account the chirp of the ionizing single attosecond pulse (attochirp) ensures that the 'clock' of our measurement technique is started at the same time for both types of electrons, revealing with high accuracy and resolution energy-dependent time delays of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 37 publications
1
92
0
Order By: Relevance
“…This is again the consequence of a propagation-induced chirp of the electron wave packet in combination with an energy-dependent transmission probability, which shifts the center of the wave packet in time without any direct physically meaningful connection to the semiclassical motion of the electron [24].…”
Section: Discussionmentioning
confidence: 99%
“…This is again the consequence of a propagation-induced chirp of the electron wave packet in combination with an energy-dependent transmission probability, which shifts the center of the wave packet in time without any direct physically meaningful connection to the semiclassical motion of the electron [24].…”
Section: Discussionmentioning
confidence: 99%
“…The collection of the streaked spectra is called a spectrogram. So far such streaking experiments have been reported for atoms, molecules, and condensed matter in numerous experiments [5][6][7][8][9][10][11]. Despite these activities, what information on the structure or the photoionization dynamics of the target can be extracted from these experiments is still rather unclear.…”
Section: Introductionmentioning
confidence: 99%
“…While the pulse duration of a typical few-cycle pulse is IR ≃ 5 fs (the period IR of an optical cycle for 800 nm radiation is IR = 2.7 fs), its oscillating field, controlled to within a small fraction of one radian, offers a convenient route to attosecond time resolution. The three different approaches utilized so far, linear momentum attosecond streaking with linearly polarized IR fields Drescher et al, 2001;Kienberger et al, 2004;Sansone et al, 2006;Cavalieri et al, 2007;Schultze et al, 2010;Sabbar et al, 2015), angular streaking ("attoclock"; Eckle et al, 2008a,b;Pfeiffer et al, 2011aPfeiffer et al, ,b, 2013 with circularly polarized IR fields, and the interferometric RABBIT technique (Paul et al, 2001;Toma and Muller, 2002;Mauritsson et al, 2005;Swoboda et al, 2010;Klünder et al, 2011;Guénot et al, 2012Guénot et al, , 2014Palatchi et al, 2014), have in common that the IR field probes the evolution during the emission, as implied by Eq. (2.18), without, however, necessarily performing a projective measurement which would lead to the "collapse of the wavepacket", i.e., to the reduction of the density operator.…”
Section: )mentioning
confidence: 99%
“…Guénot et al (2014) have reported on relative delays between argon, neon, and helium for photon energies between 31 eV and 37 eV employing RABBITT with an active stabilization of the interferometer. Sabbar et al (2015) performed streaking measurements of the relative delay between argon and neon in a photon energy region between 28 eV and 38 eV by using a gas mixture. RAB-BITT measurements for helium, neon, argon and krypton over a wider range of energies were also reported by Palatchi et al (2014).…”
Section: Time-resolved Photoionization Of Many-electron Atomsmentioning
confidence: 99%